Temas arqueológicos en debate en Argentina, 1878-1923. Dialéctica de las propuestas y objeciones acerca del pasado indígena del Noroeste - Javier Nastri (Corpus: Archivos Virtuales de la Alteridad Americana, 2022)
During the first decades of development of archaeological interest in the Argentine intellectual scene, critical exchanges arose between the practioners of the novel anthropological science. These controversies are a particularly interesting source for the study, because in them the authors, while striving to clearly expose their points of view, in their references to the opponents highlight aspects related to the dynamics of the scientific field. In this way, from the reading of the texts, a set of problems addressed in the initial stage of archaeology are defined in the present work, identifying those results obtained, and the ways that led to them. From the critical analysis of contributions and debates, the notion of the authors' choice between two alternatives in relation to the development of disciplinary work emerges. One that emphasizes the discovery and proposal of new ideas about the past; and another that places the focus on the rigorous control of the empirical bases that sustain the plausibility of the claims.